Fire safety management strategy in Nigeria public buildings - Alao Mohammed Kaseem; Yahya Mohamad Yatim; Wan Yousuf Wan Mahmood (Penerbit Universiti Kebangsaan Malaysia, 2021)
Ineffective fire safety management is one of the severe issues in public buildings, especially in Nigeria. There has been a significant increase in fire disaster cases in Nigeria in the last 25 years, the incidence of fire disasters becomes the most significant and ultimate threat to building occupants, building and its contents, as well as the economic growth of the nation. Therefore, in order to ensure the safety of building occupants, building contents, the essential features depend on the fire safety protection system, which should be under the fire safety regulation requirements. Nonetheless, practical fire safety management could remedy the damages or rates of injury in fire events. This study presents the findings on the investigation of the effectiveness of fire safety management strategy in Nigeria public buildings. This study attempts to determine the factors affecting improper fire safety management and determine the level of effective implementation of fire safety management components. From the study, safety training and adequate fire safety compliance are the factors that affect improper fire safety management the most. The level of effective implementation of fire safety management strategy is low, which translated to inadequate fire safety management. The most effective approach identified to improve the fire safety management and achievement of fire safety objectives is through effective fire safety management strategy and improvement in fire safety training arrangement and absolute compliance with the fire safety regulations.